Desempenho e fatores determinantes da arrecadação do ICMS no Estado do Ceará - Aragão, Maria Gorete Carvalho (2009)
The Tax on Goods and Services and Commodities (ICMS) is the main source of tax revenues of States, particularly in Ceará represents more than 90% of its revenues. Despite the strong growth of ICMS in the northeast region, Ceará presented results well below the others. In this scenario, this study presents a brief history and characteristics of ICMS, it is a descriptive analysis of the trend of the ICMS in Brazil, Northeast and Ceará. By presenting a different performance of other states in the region, encouraged to identify and measure the determinants of ICMS of Ceará. The methodological approach was made through a model that uses time-series data to estimate the effects on the collection of tax revenues accruing from the three largest macrossegmentos (fuel, electricity and communication services) and the level of industrial activity being measured the industrial production for the period January 1995 to September 2008. It is concluded that the low collection performance since 2000 can be explained by the performance of macrossegmentos, mainly fuel and communication services, despite the good performance recorded by GDP.